Further extension of free trade and direct taxation - Haughton, James (Statistical and Social Inquiry Society of Ireland, 1869)
At the period I refer to, some fourteen hundred articles of commerce were subjected to duties on entering the ports of Great Britain and Ireland. And now that experience, coming to the aid of sound reasoning, has proved the utter fallacy of the idea that such restrictions on commerce were wise, we are met in our efforts to carry out our sounder views to their full extent, by the self-same arguments, that there is danger and inexpediency in the course we recommend? which experience, as well as truer reasoning, has proved to have no foundation whatever. The question I am now discussing seems to me to be one of those objects which should bring us together like sensible men for effecting a good purpose? setting aside for the time being party or sectarian considerations. This purpose is one in which all are alike interested, and in which all should be alike desirous to ascertain the wisest course to pursue. Passion and prejudice cannot perhaps be wholly set aside on any subject of human discussion; but in this case surely we should not permit such feelings to prevent our cordial and general co-operation, when the knowledge and wisdom gained by experience, and by a clearer insight into those economic laws of God which govern commercial intercourse, are more generally diffused than they were even a very few years ago, and an adherence to them more generally acknowledged to be essential for promoting the peace, and happiness, and wealth of mankind.
Read Tuesday, 8th December, 1868
Keywords: Free trade in Ireland; Trade liberalisation; Customs and excise duties; Direct taxation; 314.15